Processing technology of wardrobe plate
The processing method for swimming pool more clothing cabinet panels combines tetrafluoroethylene and polyvinylidene fluoride with nanotitanium dioxide for corrosion resistance and self-cleaning, and a self-drying membrane to address corrosion and discoloration issues, ensuring the panels' longevity and hygiene.
Patent Information
- Application Number
- CN202411982847.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-28
AI Technical Summary
Existing more clothing cabinets in swimming pools, made from materials like aluminum or wood, are prone to corrosion and discoloration due to chlorine in the water, and current SMC materials suffer from residual stains and internal corrosion despite their corrosion resistance.
A processing method for more clothing cabinet panels using a composite material blend of tetrafluoroethylene, polyvinylidene fluoride, and nanotitanium dioxide for corrosion resistance, combined with a self-drying membrane on the inner side to absorb moisture and prevent corrosion.
The method provides excellent corrosion resistance, self-cleaning properties, and maintains the panel's appearance after cleaning, while the self-drying membrane protects internal items from moisture, ensuring the cabinet's longevity and hygiene.
Smart Images

Figure CN119704731A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of swimming pool accessories processing, and in particular, to a processing technology for locker panels. Background Art
[0002] In the prior art, swimming pools are usually equipped with lockers to facilitate swimming enthusiasts to change clothes and store personal belongings. Existing locker panels are usually made of aluminum alloy or wooden materials. However, since the water in the swimming pool in the swimming pool environment needs to be disinfected regularly, the swimming pool water contains a large amount of chloride ions, and chloride ions are highly corrosive. Therefore, whether the lockers are made of aluminum alloy or wooden materials, they are very easy to age. At present, they are usually protected by painting the surface, but there will be a large amount of substances harmful to the human body in the paint.
[0003] Therefore, technicians in this field have developed lockers made of SMC materials. Although they have good strength and corrosion resistance, they still have the following technical problems. Since the lockers will be cleaned regularly, the current SMC boards will leave traces on the surface after being cleaned with cleaning fluid, affecting the overall aesthetics. In addition, although they have certain corrosion resistance, since the moisture in the air contains a large amount of chloride ions, they will enter the cabinet body for a long time and cause certain corrosion to the items.
[0004] In view of this, those skilled in the art need to improve the existing processing technology of locker panels to overcome the above technical problems. Summary of the invention
[0005] The main purpose of the present application is to provide a processing technology for a locker panel, which not only has good corrosion resistance and self-cleaning properties to keep the appearance neat after cleaning, but also uses a self-drying film inside to absorb humid air in time and effectively protect the items stored inside.
[0006] In order to achieve the above-mentioned purpose, in a first aspect, the present application provides a processing technology for a wardrobe plate, comprising the following steps:
[0007] S1, processing the locker plate body, placing the raw material of the plate body in a molding die for compression molding, wherein the raw material of the plate body includes 50-60 parts of polytetrafluoroethylene, 20-30 parts of polyvinylidene fluoride, 10-15 parts of nano titanium dioxide, 20-25 parts of filler, 1-2 parts of coupling agent, 0.5-1 parts of antioxidant, and 0.5-1 parts of lubricant according to weight percentage;
[0008] S2, processing inner wall protective film, the inner wall protective film raw material is placed in a compression mold for compression molding, the inner wall protective film raw material includes 40-50 parts of polyvinyl alcohol, 20-30 parts of konjac glucomannan, 15-25 parts of moisture absorption enhancers, 5-10 parts of drying control agents, 2-5 parts of plasticizers, 0.5-1.5 parts of cross-linking agents, and 1.5-4 parts of other auxiliary agents according to weight percentage;
[0009] S3, compounding the inner wall protective film processed in step S2 onto the inner side surface of the wardrobe plate body described in step S1.
[0010] Optionally, the filler in step S1 includes 10-15 parts of glass fiber and 5-10 parts of talcum powder.
[0011] Optionally, the moisture absorption enhancer in step S2 includes 10-15 parts of lithium chloride and 5-10 parts of super absorbent resin.
[0012] Optionally, in step S2, the drying control agent is hydroxypropyl cellulose.
[0013] Optionally, in step S2, the plasticizer is glycerol.
[0014] Optionally, in step S2, in step S2, the cross-linking agent is borax.
[0015] Optionally, in step S2, the other additives include 1-3 parts of nano titanium dioxide and 0.5-1 parts of dispersant.
[0016] The processing technology of a locker plate provided by the present invention has the beneficial effects compared with the prior art. The invention adopts polytetrafluoroethylene and polyvinylidene fluoride to have good corrosion resistance and can resist chloride ion corrosion in the swimming pool environment. The polyvinylidene fluoride has good hydrophobicity and can reduce the adsorption of moisture and stains. The nano titanium dioxide is used to decompose organic pollutants so that stains on the surface of the door panel are automatically decomposed. The hardness and wear resistance of the door panel can also be improved to enhance its anti-scratch ability. Finally, a self-drying protective film is arranged on the inner side of the door panel. The konjac glucomannan thereof can absorb moisture in the air to improve its moisture absorption capacity. The polyvinyl alcohol is used to prevent the film from excessive deformation after absorbing water, thereby maintaining the overall beauty. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The drawings constituting a part of this application are used to provide a further understanding of this application, so that other features, purposes and advantages of this application become more obvious. The schematic embodiment drawings and their descriptions of this application are used to explain this application and do not constitute an improper limitation on this application. In the drawings:
[0018] Figure 1 This is a schematic diagram of the locker panel.
[0019] Among them: 1. Locker board body, 2. Inner wall protective film. DETAILED DESCRIPTION
[0020] In order to enable those skilled in the art to better understand the solution of the present application, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present application.
[0021] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequential order. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present application described here. In addition, the terms "including" and "having" and any of their variations are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device comprising a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.
[0022] In the present application, the terms "upper", "lower", "left", "right", "front", "back", "top", "bottom", "inner", "outer", "middle", "vertical", "horizontal", "lateral", "longitudinal" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the drawings. These terms are mainly used to better describe the present application and its embodiments, and are not used to limit the indicated devices, elements or components to have a specific orientation, or to be constructed and operated in a specific orientation.
[0023] In addition, some of the above terms may be used to express other meanings in addition to indicating orientation or positional relationship. For example, the term "on" may also be used to express a certain dependency or connection relationship in some cases. For those of ordinary skill in the art, the specific meanings of these terms in this application can be understood according to specific circumstances.
[0024] In addition, the term "plurality" shall mean two or more.
[0025] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0026] like Figure 1As shown, a processing technology for a locker plate includes the following steps:
[0027] S1, processing the locker plate body 1, placing the raw material of the plate body 1 in a molding die for compression molding, wherein the raw material of the plate body 1 includes 50-60 parts of polytetrafluoroethylene, 20-30 parts of polyvinylidene fluoride, 10-15 parts of nano titanium dioxide, 20-25 parts of filler, 1-2 parts of coupling agent, 0.5-1 parts of antioxidant, and 0.5-1 parts of lubricant according to weight percentage;
[0028] S2, processing the inner wall protective film 2, placing the raw material of the inner wall protective film in a molding die for compression molding, the raw material of the inner wall protective film includes 40-50 parts of polyvinyl alcohol, 20-30 parts of konjac glucomannan, 15-25 parts of moisture absorption enhancer, 5-10 parts of drying control agent, 2-5 parts of plasticizer, 0.5-1.5 parts of cross-linking agent, and 1.5-4 parts of other auxiliary agents in weight percentage; wherein the filler includes 10-15 parts of glass fiber and 5-10 parts of talc, the moisture absorption enhancer includes 10-15 parts of lithium chloride and 5-10 parts of super absorbent resin, the drying control agent is hydroxypropyl cellulose, the plasticizer is glycerol, the cross-linking agent is borax, and the other auxiliary agents include 1-3 parts of nano titanium dioxide and 0.5-1 parts of dispersant.
[0029] In step S1, polytetrafluoroethylene (PTFE) has excellent corrosion resistance and can resist the erosion of almost all chemical substances, including common cleaning liquid components. Its surface energy is extremely low and it has excellent non-stickiness, making it difficult for stains to adhere, thereby giving the door panel a self-cleaning function. At the same time, PTFE also has good high and low temperature resistance, which can adapt to the use requirements in different environments, ensuring that the locker door panel can maintain stable performance under various conditions;
[0030] Polyvinylidene fluoride (PVDF), PVDF has excellent chemical corrosion resistance, good tolerance to acids, alkalis, salts and other chemicals, and can effectively prevent cleaning fluids from corroding the door panels. It also has good mechanical strength and wear resistance, which can enhance the durability of the door panels and extend their service life. In addition, the surface of PVDF has a certain degree of hydrophobicity, which helps to reduce the adsorption of moisture and stains, further improving the self-cleaning effect;
[0031] Nano-titanium dioxide (TiO2), nano-TiO2 has photocatalytic properties, which can decompose organic pollutants under light conditions, automatically decompose stains on the surface of the door panel, and realize self-cleaning function. At the same time, it can also improve the hardness and wear resistance of the door panel, enhance its anti-scratch ability, and make the door panel less susceptible to damage in daily use. In addition, nano-TiO2 also has certain antibacterial properties, which can inhibit the growth and reproduction of bacteria on the surface of the door panel and maintain the sanitary environment in the locker;
[0032] Glass fiber has the advantages of high strength, high modulus, high temperature resistance, and corrosion resistance. It can significantly improve the mechanical strength and rigidity of the door panel and prevent the door panel from deforming during use. At the same time, the addition of glass fiber can also improve the impact resistance of the door panel, making it more durable and less likely to be damaged by collision. Talc has good lubricity and wear resistance, which can reduce the friction coefficient of the door panel surface and reduce the adhesion of stains. In addition, talcum powder can also improve the heat resistance and chemical corrosion resistance of the door panel, enhance its stability in different environments, and ensure that the performance of the door panel is not affected during long-term use;
[0033] The coupling agent can improve the interface bonding force between the main material and the filling material, improve the compatibility and dispersibility of the materials, and thus enhance the overall performance of the door panel. By using the coupling agent, the glass fiber and talcum powder can be better dispersed in the polytetrafluoroethylene and polyvinylidene fluoride matrix, giving full play to their reinforcing and wear-resistant functions, and further improving the corrosion resistance and mechanical strength of the door panel;
[0034] Antioxidants can prevent door panel materials from being degraded due to oxidation during use, thus extending their service life. When exposed to air and light for a long time, locker door panels are prone to oxidation reactions, resulting in a decrease in material performance. Adding an appropriate amount of antioxidants can effectively inhibit the occurrence of oxidation reactions and maintain the stability of the door panel's performance;
[0035] Lubricants can reduce the friction coefficient of door panel materials during processing, improve processing performance, and make the surface of door panels smoother and flatter. At the same time, lubricants can also improve the self-cleaning performance of door panels to a certain extent, making stains easier to wipe clean and reducing the difficulty of cleaning.
[0036] In step S2, polyvinyl alcohol (PVA) contains a large number of hydroxyl groups on the PVA molecular chain, has strong hydrophilicity, and can form hydrogen bonds with moisture in the air, thereby absorbing moisture. At the same time, through appropriate cross-linking modification and other treatments, its stability and mechanical properties in a humid state can be improved to prevent excessive water absorption from causing the film to dissolve or deform;
[0037] Konjac glucomannan (KGM), KGM also contains abundant hydrophilic groups and can be used as an effective component to absorb moisture from the air. It has a wide range of sources and good biocompatibility. When used in combination with PVA, it can enhance the film's ability and speed to absorb moisture and improve the film's hygroscopic properties.
[0038] Lithium chloride (LiCl), LiCl is a highly hygroscopic salt with extremely high water absorption, which can significantly increase the overall water absorption of the film. LiCl evenly dispersed in the film can absorb a large amount of water at low air humidity, further enhancing the film's ability to capture water in the air;
[0039] Highly absorbent resins, such as starch grafted acrylate polymer cross-linked products and acrylamide-acrylate copolymer cross-linked products, have extremely high water absorption and water retention capacity. They can form a gel-like state after absorbing water, which can lock the water firmly and prevent the rapid loss of water, thereby ensuring that the film continues to maintain a hygroscopic state for a certain period of time;
[0040] Hydroxypropyl cellulose (HPC) has a special phase change property. Under certain temperature conditions, it can change from a hydrophilic state to a hydrophobic state, thereby quickly releasing and collecting the absorbed water and achieving a self-drying effect. By reasonably controlling the content and distribution of HPC, the film can automatically dry under appropriate temperature or environmental conditions after absorbing enough water, restore its moisture absorption capacity, and achieve recycling;
[0041] Glycerol as a plasticizer can reduce the glass transition temperature of polymers such as PVA, increase the flexibility and fluidity of the molecular chain, make the film have better elasticity and toughness, prevent the film from cracking during moisture absorption and drying, and also help improve the processing performance and surface smoothness of the film.
[0042] Borax can cross-link with the hydroxyl groups on the PVA molecular chain to form a three-dimensional network structure, thereby improving the water resistance, mechanical strength and stability of the film. An appropriate amount of borax can keep the film in a good shape and performance in a humid environment, avoiding damage to the film structure due to excessive water absorption;
[0043] Nano-TiO2 has photocatalytic properties and can decompose organic pollutants under light conditions. It can also play a certain antibacterial role, preventing bacteria and other microorganisms from growing on the film surface, keeping the film clean and hygienic, and is conducive to the long-term and stable moisture absorption and self-drying functions of the film.
[0044] Dispersants, such as calcium stearate, are used to improve the compatibility and dispersibility between the components, ensure that various additives can be evenly dispersed in the polymer matrix, give full play to their respective properties, and improve the overall quality and performance stability of the film.
[0045] S3, compounding the inner wall protective film 2 processed in step S2 onto the inner side of the wardrobe plate body 1 described in step S1. In this step, the compounding step can be performed by hot pressing to fix the two.
[0046] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A processing technology for a locker plate, characterized in that: The following steps are involved: S1, processing the locker plate body, placing the raw material of the plate body in a molding die for compression molding, wherein the raw material of the plate body includes 50-60 parts of polytetrafluoroethylene, 20-30 parts of polyvinylidene fluoride, 10-15 parts of nano titanium dioxide, 20-25 parts of filler, 1-2 parts of coupling agent, 0.5-1 parts of antioxidant, and 0.5-1 parts of lubricant according to weight percentage; S2, processing inner wall protective film, the inner wall protective film raw material is placed in a compression mold for compression molding, the inner wall protective film raw material includes 40-50 parts of polyvinyl alcohol, 20-30 parts of konjac glucomannan, 15-25 parts of moisture absorption enhancers, 5-10 parts of drying control agents, 2-5 parts of plasticizers, 0.5-1.5 parts of cross-linking agents, and 1.5-4 parts of other auxiliary agents according to weight percentage; S3, compounding the inner wall protective film processed in step S2 onto the inner side surface of the wardrobe plate body described in step S1.
2. A processing technology for a locker plate as claimed in claim 1, characterized in that: The filler in step S1 includes 10-15 parts of glass fiber and 5-10 parts of talc.
3. The processing technology of a locker plate material according to claim 1, characterized in that: The moisture absorption enhancer in step S2 includes 10-15 parts of lithium chloride and 5-10 parts of super absorbent resin.
4. The processing technology of a locker plate material according to claim 1, characterized in that: In step S2, the drying control agent is hydroxypropyl cellulose.
5. The processing technology of a locker plate material according to claim 1, characterized in that: In step S2, the plasticizer is glycerol.
6. The processing technology of a locker plate material according to claim 1, characterized in that: In step S2, in step S2, the cross-linking agent is borax.
7. The processing technology of a locker plate material according to claim 1, characterized in that: In step S2, the other additives include 1-3 parts of nano titanium dioxide and 0.5-1 parts of dispersant.